2017
DOI: 10.2528/pierm17022207
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Coherent Micro-Doppler Imaging Method Using Hybrid Optimization

Abstract: Abstract-Conventional radar imaging methods use coherent analysis which highlights the necessity of signal phase measurement setups and complex inverse algorithms. To mitigate these drawbacks, this paper proposes a novel phase-less imaging algorithm. A nonlinear over-determined system of equations based on signal Doppler shift is developed, and a new error function originated from least square method is introduced. To obtain the exact position of targets, hybrid optimization is applied to the achieved error fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This section discusses the comparison between the presented method, and similar methods reported in the study, in terms of estimated parameters, complexity and feasibility for implementation as automotive sensor detecting pedestrians (Table III). Comparison was made between the proposed method (present paper), another micro-Doppler estimation method based on principle component analysis (PCA) (Özcan et al ., 2016), a non-coherent micro-Doppler imaging method (Safari and Abdolali, 2017), and super-resolution method based on MUSIC algorithm (Odendaal et al ., 1994). First, the proposed method and the PCA-based method are somewhat similar in their objective to classify targets; however, the methods are different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This section discusses the comparison between the presented method, and similar methods reported in the study, in terms of estimated parameters, complexity and feasibility for implementation as automotive sensor detecting pedestrians (Table III). Comparison was made between the proposed method (present paper), another micro-Doppler estimation method based on principle component analysis (PCA) (Özcan et al ., 2016), a non-coherent micro-Doppler imaging method (Safari and Abdolali, 2017), and super-resolution method based on MUSIC algorithm (Odendaal et al ., 1994). First, the proposed method and the PCA-based method are somewhat similar in their objective to classify targets; however, the methods are different.…”
Section: Discussionmentioning
confidence: 99%
“…A similar phase-less method of Doppler imaging was reported by Safari et al . ; however, their method focused on exploiting Doppler from different antenna positions to estimate the target’s position (Safari and Abdolali, 2017), whereas this present study examines the characteristics of Doppler attributed from the target’s movement. It will be demonstrated that MIMO waveforms can help in characterizing the micro-Doppler signatures of target more efficiently compared to conventional single-input single-output (SISO).…”
Section: Introductionmentioning
confidence: 99%